Synthesis and Characterization of Well-Defined Dimethylaminoethyl Methacrylate Polyelectrolytes for Non-Viral Antisense Oligonucleotides Deliveries - Jin, Xiaopin (My University, 2003)
Cationic polyelectrolytes have attracted growing attention in the field of non-viral oligonucleotides (ONs) deliveries because of their ability to bind ONs by electrostatic interactions for efficient cellular uptake. However the formation of electrostatic polymer/ONs complexes and their biological effects are still poorly understood. The relationships between polymer structure and complexation performance have not been well established. The objectives of this research are to synthesize and characterize well-defined and well-controlled cationic polyelectrolytes and to evaluate the effects of polyelectrolyte chain properties on ONs complexation. Poly(2-(dimethylamino) ethyl methacrylate) (polyDMAEMA) and its derivatives are used as the polymer candidate. A fluorescein-labeled oligonucleotide, 5 '-FGCGGAGCGTGGCAGG-3' (F: fluorescein), is used as the oligonucleotide candidate.
Low-molecular-weight cationic polyDMAEMA samples having narrow molecular weight distribution were synthesized by living anionic polymerization (LAP) and atom transfer radical polymerization (ATRP) methods. Fully charged polyDMAEMA quats were prepared by sequential quaternization of polyDMAEMA samples, as well as by direct ATRP of the quaternized DMAEMA monomer. An aqueous GPC calibration method was first developed for the characterization of these cationic polyelectrolytes. It was found that the type of counter-ion has little effect on the hydrodynamic volume of polyDMAEMA quat. Therefore the dimethyl sulfate salt of polyDMAEMA provided a reliable calibration standard for other types of quaternized DMAEMA homopolymers.
Cationic block copolymers of polyDMAEMA with 2-hydroxyethyl methacrylate (HEMA) and polyethylene glycol (PEG) were also prepared by ATRP. It was found that the order of monomer addition, solvent type, temperature, and molecular weight of macroinitiator have significant effects on the living feature of the polymerization. Well-controlled block copolymers were obtained when polyHEMA was used as the macro initiator.
The complexation capability of the prepared polyelectrolytes with oligonucleotides (15 mer) was evaluated by a fluorescence technique. It was found that the complexation performance depends on polymer molecular weight, charge density, and counter-ion type, as well as polymer concentration and block composition. The polymer sample that has double molecular weight of the ONs gave the optimal complexation performance.
Keywords: synthesis, characterization, polyelectrolytes, deliveries, antisense, non-viral, oligonucleotides, cationic, molecular weight